GE_GERICHTE P/2583/2014 vom 20. Mai 2014 - GE Cour de justice (2014)
CONFRONTATION; MESURE DE PROTECTION; DROIT D'ÊTRE ENTENDU; DROITS DE LA DÉFENSE; POUVOIR D'APPRÉCIATION | CPP.149; CPP.146; CPP.147; CPP.152